Temperature-Sensitive Mutants of Complementation Group E of Vesicular Stomatitis Virus New Jersey Serotype Possess Altered NS Polypeptides - Evans, D. (1979)
In vesicular stomatitis virus New Jersey serotype polyacrylamide gel electrophoresis was unable to distinguish the polypeptides of the temperature-sensitive (ts) mutants of complementation groups A, B, C, and F from those of the wild-type virus. However, the NS polypeptide of the representative mutant of group E, ts E1, had a significantly greater electrophoretic mobility than that of the wild-type virus NS polypeptide. The electrophoretic mobilities of the NS polypeptides of the three mutants of complementation group E varied, being greatest in the case of ts E1, slightly less for ts E2, and only a little greater than that of wild-type virus NS polypeptide in the case of ts E3. Since the NS polypeptides of the revertant clones ts E1/R1 and ts E3/R1 have mobilities identical to that of wild-type NS polypeptide, the observed altered mobilities of the group E mutants are almost certainly the direct result of the ts mutations in the E locus. The electrophoretic mobilities of the intracellular NS polypeptides of the group E mutants were indistinguishable from those of their virion NS polypeptides. The electrophoretic mobilities of the NS polypeptides of the group E mutants synthesized in vitro using mRNA synthesized in vitro by TNP were identical to those of the NS polypeptides of their purified virions. The NS polypeptides of all three mutants were labeled with (32)P(i) to approximately the same extent as wild-type virus NS polypeptide, indicating that gross differences in phosphorylation of this polypeptide are unlikely to account for the altered mobilities. We propose a model in which the NS polypeptide consists of at least three loops held in this configuration by hydrophobic or ionic forces or both and stabilized by phosphodiester bridges. If a mutation affects one of the amino acids to which the phosphate is covalently linked, the phosphodiester bridge cannot be formed, and, as a result, in the presence of sodium dodecyl sulfate the affected loop opens and thus the NS polypeptide migrates further into the gel. Such a configuration may also explain the multifunctional nature of the NS polypeptide.